THE IMPLEMENTATION ALTERNATIVE OF STORAGE POND AT GREENWOODS COUNTRY SERPONG RESIDENCE - Herprioningrum, Maharani; Andajani, Sih (INDONESIAN JOURNAL OF CONSTRUCTION ENGINEERING AND SUSTAINABLE DEVELOPMENT (CESD), 2025)
Rapid urbanization in South Tangerang has driven extensive land-use conversion into residential areas, resulting in reduced infiltration zones and increased surface runoff volume. In response to this issue, this study was conducted to address local water inundation problems in an area designated for the Greenwoods Country Serpong housing development. The planned site is traversed by a primary drainage channel that discharges into the Jaletreng River. A bottleneck at the outlet of this channel causes inundation in both the surrounding residential area and the planned development. With the upcoming construction, inundation is expected to worsen due to decreased rainwater absorption capacity, leading to increased flood discharge through the bottleneck. This study aims to design an eco-drainage system using retention and detention ponds (long storage) as an environmentally friendly and sustainable approach to stormwater management. Hydrological analysis was conducted by calculating design rainfall using four probability distribution models—Gumbel, Normal, Log-Normal, and Log-Pearson Type III—which were validated using Chi-Square and Kolmogorov-Smirnov statistical tests. Design flood discharge was estimated using the Modified Rational Method for 2-year and 5-year return periods. The study proposes six alternatives for pond dimensions, equipped with pumps, adjusted to the maximum capacity of the downstream existing channel. The results indicate that the designed storage ponds can effectively reduce flood discharge and inundation while contributing to groundwater recharge. This system offers an adaptive technical solution for residential areas with limited open space.